If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6w + 3 + -10 = 72 + -8 Reorder the terms: 3 + -10 + 6w = 72 + -8 Combine like terms: 3 + -10 = -7 -7 + 6w = 72 + -8 Combine like terms: 72 + -8 = 64 -7 + 6w = 64 Solving -7 + 6w = 64 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 6w = 64 + 7 Combine like terms: -7 + 7 = 0 0 + 6w = 64 + 7 6w = 64 + 7 Combine like terms: 64 + 7 = 71 6w = 71 Divide each side by '6'. w = 11.83333333 Simplifying w = 11.83333333
| 3y-8x=11 | | x+(x+12)=68 | | 5(4w+6)=-1 | | 3j^3+6j^2= | | 4y-12=m | | 2+5x=10-2x | | -10n=25 | | 38=-6y-7y-27 | | 3(p+3)+5p=4(2p+1)+5 | | 8y+4=24+2y | | 8g+16=7 | | 11(4p+4)-4p=(7p-7) | | 4p+4= | | x+7-12=-8 | | s^4-30s^3+260s^2-1010s+779=0 | | 6(x-1)+6x=30 | | 4y+2=182-20 | | -3.5+-12.8=x | | s^2-10s-171=0 | | 2=7(z+6) | | 7B-2=8(B+3) | | 5(v-1)=4 | | 2x-47+x=112 | | 7+c+12=-4c+12 | | 1=6(k+5) | | 7(x-4)=3(x-8) | | 4x+3=57-2x | | 2x-47=2(53)-47 | | 6r+11=15-r | | x^2+4x-94=0 | | 4-2(x+5)=4 | | 7(b-2)=4 |